2021
DOI: 10.1093/neuros/nyab195
|View full text |Cite
|
Sign up to set email alerts
|

Fields of Forel Brain Stimulation Improves Levodopa-Unresponsive Gait and Balance Disorders in Parkinson's Disease

Abstract: BACKGROUND Gait and balance disturbance are challenging symptoms in advanced Parkinson's disease (PD). Anatomic and clinical data suggest that the fields of Forel may be a potential surgical target to treat these symptoms. OBJECTIVE To test whether bilateral stimulation centered at the fields of Forel improves levodopa unresponsive freezing of gait (FOG), balance problems, postural instability, and falls in PD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Recently, burst-cycling DBS has shown similar benefits in FoG and functional mobility compared to conventional DBS but with lower battery consumption [41]. Recent meta-analyses have reported that bilateral PPN, PPN & STN, FOF, LFS SNr, HFS NST, and DN DBS combined with the levodopa approach improves gait and falls [42][43][44][45]. Conversely, bilateral open-loop GPi-DBS and closed-loop PPN-DBS were ineffective in treating FoG [46].…”
Section: Key Pointsmentioning
confidence: 99%
“…Recently, burst-cycling DBS has shown similar benefits in FoG and functional mobility compared to conventional DBS but with lower battery consumption [41]. Recent meta-analyses have reported that bilateral PPN, PPN & STN, FOF, LFS SNr, HFS NST, and DN DBS combined with the levodopa approach improves gait and falls [42][43][44][45]. Conversely, bilateral open-loop GPi-DBS and closed-loop PPN-DBS were ineffective in treating FoG [46].…”
Section: Key Pointsmentioning
confidence: 99%
“…A prospective pilot trial of directional CN-DBS is ongoing (NCT04218526). An alternative promising target has recently been proposed by Rocha et al (2021) , who reported a marked and lasting motor improvement with amelioration of PIGD in 13 PD patients with Filed of Forel DBS.…”
Section: Lead Revision and Alternative Deep Brain Stimulation Target ...mentioning
confidence: 99%
“…The authors of this paper 1 performed a prospective study of DBS of the field of Forel (FOF)—the very same area that was introduced almost exactly 60 years ago by Spiegel and Wycis and colleagues 2,3 in their original experience with stereotactic surgery for movement disorders when it was called “campotomy” and resurrected recently as a target for stereotactic lesioning. 4,5 In the authors' series, the analysis of 13 patients with advanced PD treated with FOF DBS indicated remarkable improvement of gait along with the overall improvements in PD symptoms and quality of life—and rather minor side effects that improved with DBS reprogramming.…”
mentioning
confidence: 99%